HPTLC ESTIMATION OF GALLIC ACID AND ELLAGIC ACID IN AMRTOTTARA KVATHA PREPARED IN TWO RATIOS (International Journal of Ayurveda and Pharma Research, 2019)
Amrtottara kvatha is a decoction which is used primarily in the management of hyperpyrexia (jwara). Fresh stem of Tinospora cordifolia (Willd.) Miers (Guduchi), dried fruit rind of Terminalia chebula Retz (Haritaki), and dried rhizome of Zingiber offficinale Roscoe (Shunti) in the ratio 3:2:1 are its ingredients. From the point of view of drug design, it has the peculiarity that, its ingredients are specified to be added in a particular ratio, rather than in equal amounts as is the case in most of the compound formulations in Ayurveda. But, the rationale behind the drug design are not detailed enough to give much information regarding the effect of alteration of the drug ratio etc. Thus, in the present study an exploration was made with respect to its phytochemistry, by comparing with the decoction prepared in the general ratio of 1:1:1. The compounds Gallic acid and Ellagic acid were used for quantitative evaluation and comparison using HPTLC method. Estimation of Gallic acid in the samples showed that the amount of Gallic acid in Amrtottara kvatha prepared in classical ratio of 3:2:1 is significantly higher than that prepared in the altered ratio of 1:1:1 with a p value